Novel cross-linking agent, hyaluronic acid soft tissue filling agent and preparation method

By introducing PCL/PLA molecular chains into hyaluronic acid fillers and combining the degradation mechanism of hyaluronidase, the problem of the risk of easy swelling and adverse reactions of existing fillers is solved, better mechanical properties and rapid degradation effects are achieved, and the safety and effectiveness of treatment are improved.

CN119708507AActive Publication Date: 2025-03-28SHANGHAI TONGJI HOSPITAL
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411826514.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Existing hyaluronic acid fillers have limitations in terms of filling effect and safety, such as easy swelling and weak mechanical properties, which may lead to adverse reactions and lack a mechanism for rapid degradation to cope with adverse reactions.

Method used

By introducing PCL/PLA into the hyaluronic acid cross-linking network in the form of a molecular chain, a cross-linking agent is prepared, combined with the rapid degradation mechanism of hyaluronidase, realizing immediate filling of fillers, long-term stimulation of collagen regeneration and rapid degradation.

Benefits of technology

The filler has anti-over-water absorption and swelling, better mechanical elasticity, and can rapidly degrade through hyaluronidase, reducing the risk of adverse reactions and improving the safety and effectiveness of treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708507A_ABST
    Figure CN119708507A_ABST
Patent Text Reader

Abstract

The invention provides a cross-linking agent, and the general formula of the cross-linking agent is shown as a formula (I) or a formula (II): in a # imgabs0 # formula, m is greater than or equal to 1, n is greater than or equal to 1, and l is greater than or equal to 1. According to the cross-linking agent, effective cross-linking of hyaluronic acid can be achieved by simply adjusting the pH value, excessive swelling of hyaluronic acid can be limited, the hyaluronic acid filler has good mechanical performance, supporting performance and stability, and complications are reduced. According to the cross-linking agent, PCL or PLA is introduced into a filling agent in a molecular chain mode, the advantages of PCL / PLA in the aspect of stimulating collagen and elastic fiber generation in skin are reserved, risks such as bad embolism can be rapidly treated through hyaluronidase degradation, and the treatment safety is improved. According to the scheme, a safe, reliable and high-effectiveness choice is provided for the medical cosmetology industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hyaluronic acid, and in particular to a cross-linking agent, a hyaluronic acid soft tissue filler and a preparation method thereof. Background Art

[0002] Hyaluronic acid fillers occupy an important proportion in the medical beauty market and maintain a continuous growth trend, thanks to the excellent biocompatibility and degradability of the endogenous component - hyaluronic acid. Hyaluronic acid is mainly composed of repeating units of N-acetylglucosamine and D-glucuronic acid, rich in carboxyl and hydroxyl groups, and easy to cross-link and modify. A more stable three-dimensional network structure can be formed through cross-linking. The improvement of mechanical strength provides better support for soft tissue filling, while also prolonging the degradation cycle in the body, improving and prolonging the filling and shaping effect. Hyaluronic acid can also be quickly degraded by hyaluronidase into low relative molecular mass hyaluronic acid or oligosaccharides, so as to better deal with adverse reactions or reverse suboptimal treatment results.

[0003] However, as the market pursues a higher level of filling effects, hyaluronic acid fillers have several limitations. For example, hyaluronic acid fillers are easy to swell and have weak mechanical properties, which may cause adverse reactions such as overfilling, vascular compression, deformation and displacement; biological inertness makes it unable to stimulate collagen regeneration. In contrast, the advantage of PCL or PLA microsphere fillers is that they can effectively stimulate the production of collagen and elastic fibers in the skin, thereby significantly improving skin texture and elasticity. The new filling material formed by combining PCL / PLA microspheres with hyaluronic acid fillers can have both immediate filling function and long-term stimulation of collagen regeneration function. However, the size and shape of PCL / PLA microspheres will affect their collagen regeneration effect in the body, so the regulation of their size and shape is very strict. What is more worthy of attention is that if different individuals experience adverse reactions after filling PCL / PLA microspheres, such as excessive inflammation, vascular embolism, tissue sclerosis and infection, it is difficult to correct and treat them in time. This is mainly because there is currently no effective method to quickly degrade PCL / PLA microspheres like hyaluronic acid, which brings huge potential safety risks to the application of this type of material.

[0004] Therefore, there is an urgent need for a hyaluronic acid-based filler that can achieve immediate filling and stimulate collagen regeneration, which has resistance to excessive water absorption and swelling, better mechanical elasticity, and can be quickly degraded by hyaluronidase for rapid treatment of adverse reactions. Summary of the invention

[0005] In response to the problems existing in the prior art, the present application introduces PCL / PLA into the hyaluronic acid cross-linked network in the form of molecular chains to prepare a hyaluronic acid-based filler that can achieve immediate filling and stimulate collagen regeneration. The hyaluronic acid-based filler has resistance to excessive water absorption and swelling, better mechanical elasticity, and can be rapidly degraded by hyaluronidase for rapid treatment of adverse reactions.

[0006] The present application provides a cross-linking agent, the general formula of the cross-linking agent is as shown in formula (I) or formula (II):

[0007]

[0008] In the formula, m≥1, n≥1, l≥1.

[0009] Furthermore, in the formula (I), 1≤l≤68, 1≤m≤26, 1≤n≤68, preferably 4≤l≤45, 2≤m≤18, 4≤n≤45; in the formula (II), 1≤l≤68, 1≤m≤42, 1≤n≤68, preferably 4≤l≤45, 2≤m≤28, 4≤n≤45.

[0010] Furthermore, the weight average molecular weight of the cross-linking agent represented by formula (I) is 750-9600, and the weight average molecular weight of the cross-linking agent represented by formula (II) is 700-9500; further preferably, the weight average molecular weight of the cross-linking agent represented by formula (I) is 1100-6500, and the weight average molecular weight of the cross-linking agent represented by formula (II) is 1000-6500.

[0011] The present application also provides a method for preparing the cross-linking agent, comprising:

[0012] The diblock polymer was prepared using allyl polyethylene glycol and lactone compounds as raw materials;

[0013] Carboxylated allyl polyethylene glycol was prepared using allyl polyethylene glycol and acid anhydride as raw materials;

[0014] The carboxylated allyl polyethylene glycol and the diblock polymer are reacted to prepare a triblock polymer;

[0015] The hydroxy triblock polymer is prepared by reacting mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer;

[0016] The epoxy triblock polymer, namely the crosslinking agent, is prepared by reacting epichlorohydrin, TBAB and a base with the hydroxy triblock polymer.

[0017] Furthermore, the weight average molecular weight of the allyl polyethylene glycol is 160-3000; more preferably, the weight average molecular weight is 200-2000.

[0018] Furthermore, when preparing the diblock polymer, the molar ratio of allyl polyethylene glycol to the lactone compound is preferably 1:(1-50).

[0019] Furthermore, when preparing carboxylated allyl polyethylene glycol, the molar ratio of allyl polyethylene glycol to acid anhydride is preferably 1:(1-3); and further preferably, the acid anhydride is succinic anhydride.

[0020] Furthermore, when preparing the triblock polymer, a catalyst is added to carry out the reaction; further preferably, the molar ratio of the carboxylated allyl polyethylene glycol, the catalyst and the diblock polymer is (1-2):(1-2):(2-1).

[0021] Furthermore, when preparing the hydroxy triblock polymer, the molar ratio of mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer is preferably (1-3):(1-3):1.

[0022] Furthermore, when preparing the epoxy triblock polymer, the molar ratio of epichlorohydrin, TABA, base and the triblock polymer is (3-6):(0.1-0.3):(2-5):1.

[0023] The present application provides a method for preparing a hyaluronic acid soft tissue filler, comprising: cross-linking hyaluronic acid with any of the aforementioned cross-linking agents to obtain the hyaluronic acid soft tissue filler.

[0024] Furthermore, the mass ratio of hyaluronic acid to the cross-linking agent is 1:(0.1-2); more preferably, the mass ratio is 1:(0.5-1).

[0025] Furthermore, the cross-linking reaction is carried out under alkaline conditions; more preferably, the cross-linking reaction is carried out under the condition of 9≤pH≤11.

[0026] The cross-linking agent provided in this application can achieve effective cross-linking of hyaluronic acid by simply adjusting the pH, which can limit the excessive swelling of hyaluronic acid, so that the hyaluronic acid filler has better mechanical properties, support, stability, and reduces the occurrence of complications. It is worth noting that the cross-linking agent introduces PCL or PLA into the filler in the form of a molecular chain, which not only retains the advantages of PCL / PLA in stimulating the production of collagen and elastic fibers in the skin, but also can be degraded by hyaluronidase to quickly deal with risks such as adverse embolism, thereby improving the safety of treatment. This solution provides the medical beauty industry with a safe, reliable and highly effective option. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the hydrogen nuclear magnetic resonance spectrum of the epoxy crosslinking agent described in formula (I). DETAILED DESCRIPTION

[0028] The specific embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.

[0029] The present application provides a cross-linking agent, the general formula of the cross-linking agent is as shown in formula (I) or formula (II):

[0030]

[0031] In the formula, m≥1, n≥1, l≥1.

[0032] In some embodiments, 1≤1≤68, for example, the value of l can be selected from 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68. In some preferred embodiments, it is further preferred that the value of l is 4≤1≤45.

[0033] In some embodiments, 1≤n≤68, for example, the value of n can be selected from 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68. In some preferred embodiments, it is further preferred that the value of n is 4≤n≤45.

[0034] In some embodiments, in the crosslinking agent of formula (I), 1≤m≤26, for example, the value of m can be selected from 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26. In some preferred embodiments, the value of m is further preferably 2≤m≤18.

[0035] In some embodiments, in the cross-linking agent of formula (II), 1≤m≤42, for example, the value of m can be selected from 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42. In some preferred embodiments, the value of m is further preferably 2≤m≤28.

[0036] In some embodiments, the weight average molecular weight of the cross-linking agent represented by formula (I) is 750-9600, for example, 750, 800, 900, 1000, 1100, 1300, 1500, 1800, 2000, 2200, 2500, 2800, 3000, 3200, 3500, 3800, 4000, 4200, 4500, 4800, 5000, 5200, 5500, 5800, 6000, 6200, 6500, 6800, 7000, 7200, 7500, 7800, 8000, 8200, 8500, 8800, 9000, 9200, 9500, 9600. In some preferred embodiments, the weight average molecular weight of the cross-linking agent represented by formula (I) is 1100-6500.

[0037] In some embodiments, the weight average molecular weight of the cross-linking agent represented by formula (II) is 700-9500, for example, 700, 1000, 1200, 1500, 1800, 2000, 2200, 2500, 2800, 3200, 3500, 3800, 4000, 4200, 4500, 4800, 5000, 5200, 5500, 5800, 6000, 6200, 6500, 6800, 7000, 7200, 7500, 7800, 8000, 8200, 8500, 8800, 9000, 9200, 9500. In some preferred embodiments, the weight average molecular weight of the cross-linking agent represented by formula (II) is 1000-6500.

[0038] The present application also provides a method for preparing the cross-linking agent, comprising:

[0039] Step 1: preparing a diblock polymer using allyl polyethylene glycol and a lactone compound as raw materials;

[0040] Step 2: preparing carboxylated allyl polyethylene glycol using allyl polyethylene glycol and acid anhydride as raw materials;

[0041] Step 3: the carboxylated allyl polyethylene glycol and the diblock polymer react to prepare a triblock polymer;

[0042] Step 4: preparing a hydroxy triblock polymer by reacting mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer;

[0043] Step 5: epichlorohydrin, TBAB, a base and the hydroxy triblock polymer react to prepare an epoxy triblock polymer, namely the crosslinking agent.

[0044] In step 1, when allyl polyethylene glycol and lactone compounds are used as raw materials to prepare a diblock polymer, allyl polyethylene glycol and lactone compounds are mixed under a protective atmosphere, and an initiator is added to react. The reaction time is 2-12 hours, and the reaction temperature is 100-160° C. After the reaction is completed, precipitation is carried out, and the diblock copolymer is obtained after drying for 12-36 hours.

[0045] When preparing the cross-linking agent of formula (I), the following reactions occur in the above steps.

[0046]

[0047] When preparing the cross-linking agent described in formula (II), the following reactions occur in the above steps.

[0048]

[0049] In some embodiments, the allyl polyethylene glycol is a raw material, and its weight average molecular weight is 160-3000, for example, 160, 200, 400, 700, 1000, 1200, 1500, 1700, 2000, 2200, 2500, 2700, 3000; in some preferred embodiments, its weight average molecular weight is 200-2000.

[0050] In some preferred embodiments, the lactone compound is ε-caprolactone or lactide.

[0051] In some preferred embodiments, the molar ratio of allyl polyethylene glycol to ε-caprolactone or lactide is 1:(1-50), for example 1:1, 1:3, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20, 1:22, 1:25, 1:28, 1:30, 1:32, 1:35, 1:38, 1:40, 1:42, 1:45, 1:48, 1:50.

[0052] In some preferred embodiments, the molar ratio of allyl polyethylene glycol to ε-caprolactone or lactide is 1:(14-40).

[0053] In some preferred embodiments, the initiator is stannous 2-ethylhexanoate.

[0054] In step 2, when carboxylated allyl polyethylene glycol is prepared using allyl polyethylene glycol and acid anhydride as raw materials, allyl polyethylene glycol is dissolved in an organic solvent, acid anhydride and an initiator are added to react, the reaction temperature is room temperature, the reaction time is 12-36 hours, precipitation is performed after the reaction is completed, and carboxylated allyl polyethylene glycol is obtained after drying for 12-36 hours.

[0055] When preparing the cross-linking agent described in formula (I) or formula (II), the following reaction occurs in the above steps.

[0056]

[0057] In some preferred embodiments, the anhydride is succinic anhydride.

[0058] In some preferred embodiments, the molar ratio of allyl polyethylene glycol to succinic anhydride is 1:(1-3), for example, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3.

[0059] In step three, when the carboxylated allyl polyethylene glycol and the diblock polymer react to prepare a triblock polymer, the carboxylated allyl polyethylene glycol is dissolved in an organic solvent, a catalyst and the diblock polymer are added, and the reaction is carried out under protective atmosphere conditions at room temperature for 12-36 hours. After the reaction is completed, the triblock polymer is obtained by precipitation, washing, and drying for 12-36 hours.

[0060] When preparing the cross-linking agent of formula (I), the following reactions occur in the above steps.

[0061]

[0062] When preparing the cross-linking agent described in formula (II), the following reactions occur in the above steps.

[0063]

[0064] In some preferred embodiments, the catalyst is 4-dimethylaminopyridine.

[0065] In some preferred embodiments, the molar ratio of the carboxylated allyl polyethylene glycol, the catalyst and the diblock polymer is (1-2):(1-2):(2-1), for example, the molar ratio of the carboxylated allyl polyethylene glycol and the catalyst is 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 2:1, 2:1.1, 2:1.2, 2:1.3, 2:1.4, 2:1.5 , 2:1.6, 2:1.7, 2:1.8, 2:1.9, 2:2; for example, the molar ratio of the carboxylated allyl polyethylene glycol to the diblock polymer is 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 2:1, 2:1.1, 2:1.2, 2:1.3, 2:1.4, 2:1.5, 2:1.6, 2:1.7, 2:1.8, 2:1.9, 2:2.

[0066] In some preferred embodiments, the catalyst is 4-dimethylaminopyridine.

[0067] In step 4, when mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer react to prepare a hydroxy triblock polymer, mercaptoethanol and 2,2-dimethoxy-2-phenylacetophenone are dissolved, the triblock polymer is added, and the mixture is reacted under ultraviolet light for 10-60 minutes. The hydroxy triblock polymer is obtained after washing and drying.

[0068] When preparing the cross-linking agent of formula (I), the following reactions occur in the above steps.

[0069]

[0070] When preparing the cross-linking agent described in formula (II), the following reactions occur in the above steps.

[0071]

[0072] In some preferred embodiments, the molar ratio of mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer is (1-3):(1-3):1, for example, the molar ratio of mercaptoethanol to the triblock polymer is 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1, 3:1:1 .6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1; and the molar ratio of 2,2-dimethoxy-2-phenylacetophenone to the triblock polymer is 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1.

[0073] In some preferred embodiments, the molar ratio of mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer is 2:2:1.

[0074] In step 5, when epichlorohydrin, TBAB, and a base react with the hydroxy triblock polymer to prepare an epoxy triblock polymer, the hydroxy triblock polymer is heated and melted, and epichlorohydrin and TBAB are added to react at a temperature of 30-50° C., and then a base is added. The sodium hydroxide can be added once or in multiple times, and then the epoxy triblock polymer, i.e., the crosslinking agent, is obtained by filtering, dissolving, precipitating, and drying.

[0075] When preparing the cross-linking agent of formula (I), the following reactions occur in the above steps.

[0076]

[0077] When preparing the cross-linking agent described in formula (II), the following reactions occur in the above steps.

[0078]

[0079] In some preferred embodiments, the base is NaOH.

[0080] In some preferred embodiments, the molar ratio of epichlorohydrin, TBAB, NaOH and the hydroxy triblock polymer to prepare the epoxy triblock polymer is 3-6:0.1-0.3:2-5:1, for example,

[0081] The molar ratio of epichlorohydrin to the hydroxy triblock polymer is 3:1, 4:1, 5:1, 6:1; the molar ratio of TABA to the hydroxy triblock polymer is 0.1:1, 0.2:1, 0.3:1; the molar ratio of NaOH to the hydroxy triblock polymer is 2:1, 3:1, 4:1, 5:1.

[0082] In some preferred embodiments, the molar ratio of epichlorohydrin, TBAB, NaOH and the hydroxy triblock polymer to prepare the epoxy triblock polymer is 5:0.2:3:1.

[0083] In some embodiments, the organic solvent used in steps 1 to 5 is 1,4-dioxane and / or dichloromethane.

[0084] In some embodiments, the protective atmosphere in steps 1 to 5 is nitrogen.

[0085] In some embodiments, the drying in steps 1 to 5 can be vacuum drying or freeze drying.

[0086] The present application provides a method for preparing a hyaluronic acid soft tissue filler, comprising: subjecting hyaluronic acid to a cross-linking reaction with the above-mentioned cross-linking agent to obtain the hyaluronic acid soft tissue filler.

[0087] Furthermore, the hyaluronic acid and the cross-linking agent are mixed and dissolved according to a mass ratio, and a base is added to carry out a cross-linking reaction. The reaction temperature is 20-50° C. and the reaction time is 2-12 hours. The hydrogel product is obtained after washing. The hydrogel product is washed to remove unreacted BDDE to obtain the hyaluronic acid soft tissue filler.

[0088] When the hyaluronic acid soft tissue filler is prepared using the cross-linking agent described in formula (I), the following reaction occurs.

[0089]

[0090] When the hyaluronic acid soft tissue filler is prepared using the cross-linking agent described in formula (II), the following reaction occurs.

[0091]

[0092] In some embodiments, the mass ratio of hyaluronic acid to the cross-linking agent is 1:(0.1-2), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.

[0093] In some preferred embodiments, the mass ratio of hyaluronic acid to the cross-linking agent is 1:(0.5-1).

[0094] In some embodiments, the cross-linking reaction is carried out under alkaline conditions of pH>7. In some preferred embodiments, the cross-linking reaction is carried out under conditions of 9≤pH≤11.

[0095] Example

[0096] The experimental methods used in the following examples are all conventional methods unless otherwise specified.

[0097] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0098] Example 1

[0099] Preparation of APEG-PCL-OH diblock polymer: 8 g of allyl polyethylene glycol (0.004 mol), 13.7 g of ε-caprolactone (0.12 mol) and 0.3 g of stannous 2-ethylhexanoate were added to a 250 ml three-necked flask under nitrogen atmosphere and mechanical stirring, and refluxed at 130 ° C for 8 hours. After the reaction was completed, 100 ml of ether was used for precipitation, and the product was filtered and vacuum dried for 24 hours to obtain APEG-PCL-OH diblock copolymer.

[0100] Preparation of carboxylated APEG: 6 g of allyl polyethylene glycol (0.003 mol) was dissolved in 25 ml of 1,4-dioxane, and then 0.48 g of succinic anhydride (0.0048 mol) and 0.37 g of 4-dimethylaminopyridine (0.003 mol) were added to the solution. After stirring the reaction at room temperature for 24 hours, 100 ml of ether was used for precipitation, and the product was vacuum dried for 24 hours to obtain carboxylated APEG.

[0101] Preparation of APEG-PCL-APEG: 3g APEG-COOH (0.0014mol) was dissolved in 30ml dichloromethane and stirred at room temperature for 30 minutes, then 1.2g 4-dimethylaminopyridine (0.0014mol) was added, 4.05g APEG-PCL-OH (0.001mol) was added to the reaction mixture, and the reaction was stirred for 24 hours at room temperature under nitrogen atmosphere, and then precipitated with 100ml ether and dialyzed with water to remove unreacted residual PEG-COOH, and finally freeze-dried for 24 hours to obtain APEG-PCL-APEG triblock copolymer.

[0102] Preparation of hydroxy PEG-PCL-PEG: After completely dissolving 0.076 g of mercaptoethanol (0.000978 mol) and 0.25 g of 2,2-dimethoxy-2-phenylacetophenone (0.000978 mol) in 30 ml of ethanol, 3 g of APEG-PCL-APEG (0.000489 mol) was added to the above solution, mixed well, and the above solution was stirred for reaction under ultraviolet light for 30 minutes, then dialyzed with water for 3 days to remove unreacted residual reactants, and finally lyophilized to obtain hydroxy PEG-PCL-PEG triblock copolymer.

[0103] Preparation of epoxy PEG-PCL-PEG: 2g hydroxy PEG-PCL-PEG triblock copolymer (0.000318mol) was heated to melt, 0.146g epichlorohydrin (0.00159mol) and 0.02g TBAB (0.000064mol) were added to react at 40 degrees Celsius, 0.038g sodium hydroxide (0.000954mol) was added in portions after a period of time, and the mixture was filtered while hot, the dichloromethane was melted, ether was precipitated, and the epoxy triblock polymer, i.e., the crosslinking agent, was obtained by vacuum drying. Finally, the epoxy PEG-PCL-PEG triblock copolymer was obtained by freeze drying.

[0104] Compared with Example 1, the only difference between Examples 2-3 is that when preparing the diblock polymer, the weight average molecular weight of the allyl polyethylene glycol is different, thereby preparing different epoxy PEG-PCL-PEG crosslinkers, and the other parameters are the same.

[0105] Compared with Example 1, the only difference between Examples 4-5 is that when preparing carboxylated APEG, the weight average molecular weight of allyl polyethylene glycol is different, thereby preparing different epoxy PEG-PCL-PEG crosslinkers, and the other parameters are the same.

[0106] Compared with Example 1, the only difference between Examples 6-7 is that when preparing the diblock polymer, the molar ratio of allyl polyethylene glycol to ε-caprolactone is different, thereby preparing different epoxy PEG-PCL-PEG crosslinkers, and the other parameters are the same.

[0107] Compared with Example 1, the only difference in Example 8 is that, when preparing the diblock polymer, ε-caprolactone is replaced with lactide to prepare an epoxy PEG-PLA-PEG crosslinker, and the other parameters are the same.

[0108] Compared with Example 8, the only difference between Examples 9-10 is that when preparing the diblock polymer, the molar ratio of allyl polyethylene glycol to lactide is different, thereby preparing different epoxy PEG-PLA-PEG crosslinkers, and the other parameters are the same.

[0109] The epoxy triblock copolymers obtained in Examples 1-10 were tested in the following manner.

[0110] 1. Chemical structure characterization

[0111] After the raw materials were dissolved in deuterated chloroform, the chemical structure of the obtained copolymer was characterized by hydrogen nuclear magnetic resonance spectroscopy.

[0112] 2. Calculate the epoxy value

[0113] The epoxy value of the epoxy triblock copolymer was titrated using the hydrochloric acid-acetone method. Taking Example 1 as an example, the specific operation was as follows: 1 g of the epoxy triblock copolymer obtained by freeze-drying was accurately weighed and placed in a 250 mL stoppered conical flask, and 20 mL of hydrochloric acid-acetone solution was added and sealed. After shaking well, it was placed in a dark place and allowed to stand for 30 minutes. 5 drops of mixed indicator solution (10 mL of cresol red, 30 mL of thymol blue, 0.01 mol / L sodium hydroxide and 0.01 mol / L hydrochloric acid adjusted to neutral) were added, and 0.15 mol / L sodium hydroxide standard titration solution was used to titrate to purple-blue, and the volume of the sodium hydroxide standard titration solution consumed was recorded, and the epoxy value was obtained by calculation.

[0114] according to Figure 1 It can be seen that the peak with a chemical shift of about 4.05 corresponds to the hydrogen of the repeating unit in polyethylene glycol, the peaks with chemical shifts of about 2.25, 1.8, and 1.4 correspond to the hydrogen at the d, e, and f positions in polycaprolactone, and the two peaks at about 2.75 correspond to the hydrogen at the a and b positions on the epoxy group. At the same time, combined with the epoxy value calculated by the hydrochloric acid-acetone titration method, the successful preparation of the epoxy triblock crosslinker can be confirmed.

[0115] 3. Detection of molecular weight

[0116] The weight average molecular weight and the degree of polymerization n, m, and l of the epoxy triblock copolymer were measured using a gel permeation chromatograph.

[0117] The parameters of Examples 1-10 and the test results of the prepared cross-linking agents are shown in Table 1.

[0118] Wherein, when preparing the diblock polymer, the weight average molecular weight of the allyl polyethylene glycol used is recorded as Mw1;

[0119] When preparing carboxylated APEG, the weight average molecular weight of the allyl polyethylene glycol used is denoted as Mw2;

[0120] When preparing the diblock polymer, the molar ratio of allyl polyethylene glycol to lactone is recorded as "x:y";

[0121] The weight average molecular weight of the epoxy triblock copolymer is denoted as Mw3;

[0122] "n:m:l" refers to the ratio of n, m, and l in the epoxy triblock copolymer.

[0123] Table 1

[0124] Mw1 Mw2 Lactone x:y n:m:l Mw3 Epoxy value Example 1 2000 2000 ε-Caprolactone 1:30 44:18:44 6440 0.305 Example 2 700 2000 ε-Caprolactone 1:30 15:18:44 5240 0.374 Example 3 1500 2000 ε-Caprolactone 1:30 32:18:44 6010 0.333 Example 4 2000 700 ε-Caprolactone 1:30 44:18:15 5230 0.385 Example 5 2000 1500 ε-Caprolactone 1:30 44:18:32 6000 0.335 Example 6 2000 2000 ε-Caprolactone 1:15 44:10:44 5510 0.361 Example 7 2000 2000 ε-Caprolactone 1:37 44:26:44 7360 0.272 Example 8 2000 2000 Lactide 1:30 44:18:44 5720 0.352 Example 9 2000 2000 Lactide 1:15 44:10:44 5160 0.389 Example 10 2000 2000 Lactide 1:37 44:26:44 6280 0.369

[0125] Embodiment 11

[0126] Preparation of hyaluronic acid filler: 0.1 g HA powder was dissolved in 10 ml deionized water containing 0.1 g epoxy PEG-PCL-PEG and 2.5 g NaOH, and the mixture was reacted at 40 ° C for 6 h. The reaction mixture was washed with deionized water for 3 times to obtain a hydrogel product. The hydrogel was dialyzed with phosphate buffer for 24 h and then with deionized water for 24 h to completely remove unreacted BDDE.

[0127] In this embodiment, the cross-linking agent is an epoxy PEG-PCL-PEG triblock copolymer, which is prepared by the method described in Example 1.

[0128] Compared with Example 11, Examples 12-20 differ in that the epoxy triblock copolymers prepared in Examples 2-10 are respectively used as cross-linking agents to prepare hyaluronic acid fillers, and other parameters are the same.

[0129] Compared with Example 11, Examples 21-22 differ in that the mass ratios of hyaluronic acid and cross-linking agent are different, namely 1:0.5, 1:0.8, and 1:1.2, respectively, and other parameters are the same.

[0130] Comparative Example 1

[0131] Compared with Example 11, the only difference of Comparative Example 1 is that PCL microspheres are used as a cross-linking agent to prepare the hyaluronic acid filler, and the hyaluronic acid used in this embodiment is the same as that in Example 11.

[0132] Comparative Example 2

[0133] The only difference between Comparative Example 2 and Comparative Example 1 is that the hyaluronic acid filler is prepared using PLA microspheres as a cross-linking agent in Comparative Example 2, and the other parameters are the same.

[0134] The hyaluronic acid fillers in Examples 11-22 and Comparative Examples 1-2 were tested as follows.

[0135] The viscoelasticity G of the hyaluronic acid filler was tested by a rotational rheometer, including the elastic modulus G' and the loss modulus G", the unit is Pa. Among them, G' refers to the elastic properties of the material, that is, the ability of the material to return to its original shape after being subjected to external force. The elastic modulus directly reflects the ability of the material to store and release energy. Generally speaking, the larger the elastic modulus, the stronger the rigidity of the material. G" refers to the damping properties of the material, that is, the degree of energy loss of the material when subjected to external force. The size of the loss modulus directly affects the vibration attenuation ability of the material. Generally speaking, the larger the loss modulus, the more obvious the viscous behavior of the material. The viscoelasticity test conditions are to select a 12mm fixture, test at 37°C, and the test mode is Oscillation Frequency Sweep Test. ;

[0136] The swelling coefficient of the hyaluronic acid filler was tested by the weighing method. The hydrogel sample was immersed in deionized water for at least 24 hours, then quickly taken out of the water, and the surface water was removed with filter paper and weighed to obtain the equilibrium swelling mass Ws of the sample. The equilibrium swelling rate (ESR) of the hydrogel was calculated by the following formula: ESR = Ws / Wd, where Wd is the dry weight of the gel.

[0137] The degradation cycle of hyaluronic acid fillers was tested in vitro using simulated body fluids, with PBS as the degradation medium and 37°C as the degradation temperature.

[0138] The test results of the hyaluronic acid fillers in Examples 11-25 and Comparative Examples 1-2 are shown in Table 2.

[0139] Table 2

[0140]

[0141]

[0142] Comparing the data in Table 1 and Table 2, it can be seen that by adjusting the feed ratio and controlling the reaction conditions, an epoxy crosslinker with a specific molecular structure can be synthesized. The more PCL / PLA components in the epoxy crosslinker, the stronger the ability to limit swelling. This is because PCL / PLA are both hydrophobic, so the hydrophilicity of the weakened gel limits the swelling degree. At the same time, the degradation cycle also changes with the change of PCL / PLA content, and both types of molecules can extend the degradation cycle of the filler.

[0143] The hyaluronic acid filler prepared in the present application significantly limits the swelling of hyaluronic acid, and at the same time abandons the use of traditional organic solvents in the preparation process, thereby reducing the environmental burden and potential health risks in the production process.

[0144] The cross-linking agent prepared in this application retains the advantages of PCL / PLA in stimulating the production of collagen and elastic fibers in the skin, and improves the safety of treatment. This solution provides a safer, more reliable and more effective option for the medical beauty industry.

[0145] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0146] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A cross-linking agent, the general formula of which is as shown in formula (I) or formula (II): In the formula, m≥1, n≥1, l≥1.

2. The crosslinking agent according to claim 1, wherein In the formula (I), 1≤l≤68, 1≤m≤26, 1≤n≤68, preferably 4≤l≤45, 2≤m≤18, 4≤n≤45, or In the formula (II), 1≤l≤68, 1≤m≤42, 1≤n≤68; preferably 4≤l≤45, 2≤m≤28, 4≤n≤45.

3. The crosslinking agent according to claim 1, wherein The weight average molecular weight of formula (I) is 750-9600, preferably 1100-6500; or The weight average molecular weight of the formula (II) is 700-9500, preferably 1000-6500.

4. A method for preparing a cross-linking agent, wherein: include: The diblock polymer was prepared using allyl polyethylene glycol and lactone compounds as raw materials; Carboxylated allyl polyethylene glycol was prepared using allyl polyethylene glycol and acid anhydride as raw materials; The carboxylated allyl polyethylene glycol and the diblock polymer are reacted to prepare a triblock polymer; The hydroxy triblock polymer is prepared by reacting mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer; The epoxy triblock polymer is prepared by reacting epichlorohydrin, TBAB and a base with the hydroxy triblock polymer to obtain a crosslinking agent.

5. The preparation method according to claim 4, wherein: The weight average molecular weight of the allyl polyethylene glycol is 160-3000, preferably 200-2000.

6. The preparation method according to claim 4, wherein: When preparing the diblock polymer, the molar ratio of the allyl polyethylene glycol to the lactone compound is 1:(1-50); or When preparing carboxylated allyl polyethylene glycol, the molar ratio of the allyl polyethylene glycol to the acid anhydride is 1:(1-3); or preferably the acid anhydride is succinic anhydride; or When preparing the triblock polymer, the carboxylated allyl polyethylene glycol and the diblock polymer react under the action of a catalyst; preferably, the molar ratio of the carboxylated allyl polyethylene glycol, the catalyst and the diblock polymer is (1-2):(1-2):(2-1); or When preparing the hydroxy triblock polymer, the molar ratio of the mercaptoethanol, 2,2-dimethoxy-2-phenylacetophenone and the triblock polymer is (1-3):(1-3):1; or When preparing the epoxy triblock polymer, the molar ratio of epichlorohydrin, TABA, base and the triblock polymer is (3-6):(0.1-0.3):(2-5):

1.

7. The preparation method according to any one of claims 4 to 6, wherein: The cross-linking agent prepared by the preparation method is the cross-linking agent according to any one of claims 1 to 3.

8. A hyaluronic acid soft tissue filler, wherein: The invention comprises the cross-linking agent described in any one of claims 1 to 3 or the cross-linking agent prepared by the preparation method described in any one of claims 4 to 7.

9. The filler according to claim 8, wherein The filler further comprises hyaluronic acid, and the hyaluronic acid undergoes a cross-linking reaction with the cross-linking agent to obtain a hyaluronic acid soft tissue filler.

10. The filler according to claim 9, wherein: The mass ratio of the hyaluronic acid to the cross-linking agent is 1:(0.1-2); preferably 1:(0.5-1).

Citation Information

Patent Citations

  • Mixed gel containing amphiphilic microspheres and preparation method thereof

    CN114917411A

  • Biodegradable epoxy cross-linking agent as well as preparation method and application thereof

    CN116063253A

  • Copolymer hydrogel of polycaprolactone polyethylene glycol and derivatives thereof as well as preparation method and application of copolymer hydrogel

    CN116355238A

  • Preparation method and application of polymer microspheres capable of injecting, loading and cross-linking hyaluronic acid

    CN117442779A

  • Epoxy crosslinking agent and its prepn and application in preparing biodegradable material

    CN1417253A